Thermal Comfort Satisfaction Analysis at The Natural Ventilated Non-Air Conditioner Gymnasium - Rahmat, Muhamad Hanafi; Mohamad Shahrul Azizi Saadon (Recent Trends in Civil Engineering and Built Environment, 2020)
In recent years, people’s inclination to go to the gym has increased as people begin to care more about a healthy lifestyle. A gym is a sports facility that can be defined as space in a building used for indoor sports activities. Thermal comfort at the gym affects employees in terms of health, productivity, and satisfaction. External environmental conditions also have a significant impact on non-air-conditioned buildings. It is important to know the level of thermal comfort in the gym in ensuring the comfort and efficiency of gym users while doing sports activities in the gym. This study was conducted to analyze the impact of outdoor environmental conditions from different times on the level of thermal comfort of the occupants and evaluate the best time to go to the gym based on the level of thermal comfort of the gym. The method used for this study was the thermal comfort assessment performed inside the gym. The environments examined were relative humidity (%), air velocity (m/s), air temperature, and radiant temperature (° C). Environmental factor data were collected using the portable anemometer. The thermal comfort of gym occupants was assessed using a thermal sensation scale using Prediction Mean Vote (PMV) and Prediction Percentage Dissatisfied (PPD) which was used to estimate the satisfaction and level of thermal comfort. Calculation of PMV and PPD values were done ​​using the CBE thermal comfort tool. The results of the evaluation had shown that the value of PMV at noon and evening was higher than at night. This indicated that at night had a better level of thermal comfort. All PMV values ​​calculated were positive values, an indication that the occupants were experiencing a hot environment in the gym. All PMV values ​​did not fall in the comfort zone even though the environment was good. All the PPD value not in a good range which showed that most of the occupants were dissatisfied with the gym thermal condition. In conclusion, the results obtained in this naturally ventilated gym without air conditioning were not able to meet a good level of thermal comfort.